The Authority Of The DPR On The Appointment and Dismissal of Constitutional Judges - Prasetyo, Iwan Kurniawan; Azzahra, Humaira; Huda, Khazanatul (Program Studi Magister Kenotariatan Fak. Hukum Univ. Andalas, 2023)
Based on the 1945 Constitution, 3 institutions are authorized to appoint constitutional judges, including the Representative Council, Supreme Court, and the President. In the event that the dismissal of constitutional judges can be carried out if they have fulfilled the criteria contained in article 23 of Law No.7/2020. Paragraph (4) of the same article confirms that those with authority to dismiss a constitutional judge are the Chief Justices of the Constitutional Court and the President. However, in 2022 there is a polemic, namely the form of intervention against the dismissal of constitutional judges carried out by one of the legislative bodies, namely the Representative Council of Indonesia, which is a big question mark. What kind of authority does the Representative Council have as a legislature over the CC? Is this action justifiable and in accordance with applicable law? This legal research with a normative juridical approach examines secondary data in books, journals, and legislation as a reference. The result of this study indicates that the Representative Council’s over CC as contained in the 1945 Constitutions is very limited in proposing 3 candidates for constitutional judges and has no authority at all to dismiss them. The Representative Counsil’'s decision to dismiss constitutional judges is an act of offending the principle of the independence of the Constitutional Court and has no legal basis.